Ocular Immune Privilege and Transplantation - Taylor, Andrew W. (Frontiers in Immunology, 2016)
Allografts are afforded a level of protection from rejection within immune privileged tissues. Immune privileged tissues involve mechanisms that suppress inflammation, and promote immune tolerance. There are anatomical features, soluble factors, membrane associated proteins, and alternative antigen presenting cells that contribute to allograft survival in the immune privileged tissue. This review presents the current understanding of how the mechanism of ocular immune privilege promote tolerogenic activity by antigen presenting cells, and T cells in response to the placement of foreign antigen within the ocular microenvironment. Discussed will be the unique anatomical, cellular and molecular mechanisms that lessen the chance for a graft destroying immune responses within the eye. As more is understood about the molecular mechanisms of ocular immune privilege greater is the potential in using these molecular mechanisms in therapies to prevent allograft rejection.